The Effect of Special Exercises in the Intermittent Style (Short – Short) on Some Physical and Skill Abilities of Youth Football Players - Arshed Dhafer Abdusahlb (Sinar Sport Journal, 2025)
Football is one of the games that has witnessed a remarkable development in the performance of players and their ability to provide distinct levels through their ability to provide the best skill level throughout the game, which indicates the development of their various physical and skill capabilities. There are many and varied exercises that helped in the development of this game, and one of these exercises is the use of (intermittent exercises ( short – short), which is based on exercises that are close to the player's performance during the game, the goal of the study is to prepare exercises in the intermittent style ( short – short ) and their impact on the development of some physical abilities (maximum speed, explosive power, strength marked by speed ) and skill( rolling, handling and scoring ) for youth football players . The researcher used the experimental method using the method of equal groups on the players of the agreement Sports Football Club, numbering (20) young people after the sample was divided into two experimental and control groups, with ( 10 ) players for each group, and the two groups were equated with the study variables , and the group underwent special exercises in the intermittent style ( short – short) for (8) week and with (3) training units per week, and through the results, the researcher concluded that – Short) a positive impact on the development of some physical and skill abilities under study (maximum speed, explosive power, speed-marked strength) and some skills ( rolling, handling and scoring)